Formulasi Basis Sheet Mask Bioselulosa - Nathania Ramadhanty Nuzirwan; Gita Cahya Eka Darma; Anan Suparman (Bandung Conference Series: Pharmacy, 2022)
Abstract. There are environmental aggressors such as UV-rays and micro/nano particles indoors or outdoors can cause damage to skin collagen/elastin that triggers premature aging. Based on these things, there is a demand for innovative cosmetic product formulations, capable of neutralizing the negative effects of UV rays, and made from natural ingredients. Biocellulose sheet masks are obtained from natural sources, namely the bacterium Acetobacter xylinum which produces acid from glucose and synthesizes cellulose. The purpose of this study was to obtain a biocellulose sheet mask formulation with best characteristics, as well as to compare the ability to moisturize biocellulose sheet mask and non-woven sheet mask. The formulation of the biocellulose sheet mask has a good characteristics. The results of comparison between biocellulose sheet masks and non woven sheet masks show that biocellulose sheet masks has the best skin moisturizing effect. Abstrak. Agresor lingkungan seperti sinar UV dan mikro/nano partikulat terdapat di luar maupun di dalam ruangan dapat menyebabkan kerusakan kolagen/elastin kulit yang pemicu penuaan dini. Berdasarkan hal-hal tersebut terbentuklah permintaan untuk formulasi produk kosmetik yang inovatif, mampu menetralisir efek negatif sinar UV, dan dibuat dari bahan-bahan alami. Sheet mask bioselulosa diperoleh dari sumber alami yaitu bakteri Acetobacter xylinum yang menghasilkan asam dari glukosa dan mensintesis selulosa. Tujuan dari penelitian ini yaitu untuk mendapatkan formulasi sheet mask bioselulosa dengan karakteristik baik, serta mengetahui perbandingan kemampuan melembabkan sheet mask bioselulosa dan sheet mask non woven. Formulasi sheet mask bioselulosa yang dihasilkan memiliki karakteristik baik. Hasil komparasi sheet mask bioselulosa dan sheet mask non woven diketahui bahwa sheet mask bioselulosa memiliki efek melembabkan yang lebih baik dibandingkan dengan sheet mask non woven.